The pharaoh's secret [compact disc, unabridged] : a novel from the Numa files - Cussler, Clive (Cussler, Clive. NUMA files., 2015)
The dazzling new novel in the bestselling NUMA Files series from the grand master of adventure. Kurt and Joe tangle with the most determined enemy they've ever encountered when a ruthless powerbroker schemes to build a new Egyptian empire as glorious as those of the Pharaohs. Part of his plan rests on the manipulation of a newly discovered aquifer beneath the Sahara, but an even more devastating weapon at his disposal may threaten the entire world: a plant extract known as the black mist rumoured to have the power to take life from the living and restore it to the dead. Kurt, Joe, and the rest of the NUMA team will have to fight to discover the truth behind the legends - but to do that, they have to confront in person the greatest legend of them all: Osiris, the ruler of the Egyptian underworld.